Discovery and Use of Long dsRNA Mediated RNA Interference to Stimulate Antiviral Protection in Interferon Competent Mammalian Cells - Semple, Shawna L.; Au, Sarah K. W.; Jacob, Rajesh A.; Mossman, Karen L.; DeWitte-Orr, Stephanie J. (Frontiers in Immunology, 2022)
In invertebrate cells, RNA interference (RNAi) acts as a powerful immune defense that stimulates viral gene knockdown thereby preventing infection. With this pathway, virally produced long dsRNA (dsRNA) is cleaved into short interfering RNA (siRNA) by Dicer and loaded into the RNA-induced silencing complex (RISC) which can then destroy/disrupt complementary viral mRNA sequences. Comparatively in mammalian cells, it is believed that the type I interferon (IFN) pathway is the cornerstone of the innate antiviral response. In these cells, dsRNA acts as a potent inducer of the IFN system, which is dependent on dsRNA length, but not sequence, to stimulate an antiviral state. Although the cellular machinery for RNAi is intact and functioning in mammalian cells, its role to trigger an antiviral response using long dsRNA (dsRNAi) remains controversial. Here we show that dsRNAi is not only functional but has a significant antiviral effect in IFN competent mammalian cells. We found that pre-soaking mammalian cells with concentrations of sequence specific dsRNA too low to induce IFN production could significantly inhibit viral replication with vesicular stomatitis virus expressing green fluorescent protein (VSV-GFP), and the human coronaviruses (CoV) HCoV-229E and SARS-CoV-2. This phenomenon was shown to be dependent on dsRNA length, was comparable in effect to transfected siRNAs, and could knockdown multiple sequences at once. Additionally, knockout cell lines revealed that functional Dicer was required for viral inhibition, revealing that the RNAi pathway was indeed responsible. These results provide the first evidence that soaking with gene-specific dsRNA can generate viral knockdown in mammalian cells. We believe that this novel discovery provides an explanation as to why the mammalian lineage retained its RNAi machinery and why vertebrate viruses have evolved methods to suppress RNAi. Furthermore, demonstrating RNAi below the threshold of IFN induction has uses as a novel therapeutic platform, both antiviral and gene targeting in nature.